2007
DOI: 10.1007/s12019-007-0011-3
|View full text |Cite
|
Sign up to set email alerts
|

Health-Seeking Behaviors and Sexually Transmitted Diseases Among Adolescents Attending An Urban Pediatric Emergency Department

Abstract: This study confirms a high prevalence of treatable STDs among adolescents in an urban ED setting and provides information on frequency of ED usage and health-seeking behaviors among adolescents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
7
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 19 publications
2
7
0
Order By: Relevance
“…In general, there is little recent data characterizing the overall prevalence of STIs in the adolescent ED population, 40,62 given limitations in surveillance and variations in which types of STIs are queried. However, we found that among adolescents in the ED who had ever been sexually active, 10% self-reported a prior STI and over half engaged in high risk sexual behaviors.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In general, there is little recent data characterizing the overall prevalence of STIs in the adolescent ED population, 40,62 given limitations in surveillance and variations in which types of STIs are queried. However, we found that among adolescents in the ED who had ever been sexually active, 10% self-reported a prior STI and over half engaged in high risk sexual behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…35 For example, studies involving point-of-care testing have shown that about 11% of youth in EDs tested positive for chlamydia or gonorrhea. 39,40 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…9 Among male and female adolescents seeking care in urban EDs, rates of chlamydial and/or gonorrheal infection of 8-25% have been reported. 10-12 …”
Section: Introductionmentioning
confidence: 99%
“…Chlamydia is one of the most common sexually transmitted infections (STIs) in sexually active women, has a high prevalence in the ED setting, [7][8][9] and is frequently asymptomatic. 6,7,10 The objective of this study was to evaluate the feasibility of chlamydia screening using a model in which the ED is responsible for collection of urine samples, and the PHD completes the testing, follow-up, and treatment.…”
mentioning
confidence: 99%